Answer:
the solution to the system of equation is;
![\begin{gathered} x=7 \\ y=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zq73coc687q10vojroxqklpwcnd2ahx3ie.png)
Exp
Given the system of equation;
![\begin{gathered} x-4y=-13\text{ --------1} \\ x-2y=-3\text{ --------2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qnyqgbh7qod6fqehgai84dcop7ercfjwem.png)
We want to solve by elimination.
subtract equation 1 from equation 2;
![\begin{gathered} x-x-2y-(-4y)=-3-(-13) \\ -2y+4y=-3+13 \\ 2y=10 \\ \text{divide both sides by 2;} \\ (2y)/(2)=(10)/(2) \\ y=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1q2yj0wkg0kmoiseva86dt5mq63jgyc92t.png)
If y=5, then the value of x can be derived using equation 2 as;
![\begin{gathered} x-2y=-3 \\ x-2(5)=-3 \\ x-10=-3 \\ x=-3+10 \\ x=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/davtr4i9i048jv31kdrx913eh5f93cysm1.png)
Therefore, the solution to the system of equation is;
![\begin{gathered} x=7 \\ y=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zq73coc687q10vojroxqklpwcnd2ahx3ie.png)